2005
DOI: 10.1111/j.1365-2249.2005.02920.x
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin glycoprotein ligand-1 (PSGL-1) is up-regulated on leucocytes from patients with chronic obstructive pulmonary disease

Abstract: SummaryChronic obstructive pulmonary disease (COPD) is characterized by a dysregulated recruitment of circulating leucocytes into the lung which is associated with the onset and progress of the disease. P-selectin glycoprotein ligand-1 (PSGL-1) is expressed on leucocytes and plays an essential role in primary leucocyte-endothelial cell adhesive contacts. The present study investigated if PSGL-1 is up-regulated on leucocytes of COPD patients. Peripheral blood samples were collected from COPD patients as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…We found that PSGL-1 expression itself was up-regulated following the activation of CLA + CD4 + T cells. Others have also shown that surface expression of PSGL-1 can be up-regulated upon T cell stimulation in an antigen specific manner using TCR transgenic mice [44,45]. Moreover, we found that CHO-131 directly recognized PSGL-1 and the expression of C2-O-sLe X -modified PSGL-1 significantly increased following the activation of CLA + CD4 + T cells.…”
Section: Discussionsupporting
confidence: 68%
“…We found that PSGL-1 expression itself was up-regulated following the activation of CLA + CD4 + T cells. Others have also shown that surface expression of PSGL-1 can be up-regulated upon T cell stimulation in an antigen specific manner using TCR transgenic mice [44,45]. Moreover, we found that CHO-131 directly recognized PSGL-1 and the expression of C2-O-sLe X -modified PSGL-1 significantly increased following the activation of CLA + CD4 + T cells.…”
Section: Discussionsupporting
confidence: 68%
“…Contradictory to this finding, a small study of subjects with varying stages of COPD (GOLD I-IV) found increased CD162 expression on circulating neutrophils in the COPD group [28]. The ligand of CD162, P-selectin, has received attention as a marker of platelet activation and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported increased CD162 [11], no differences in CD11a and CD62L [12-15] and both increased [12,14,16,17] and unchanged [14,15] CD11b on neutrophils in COPD. These discrepant results are likely due to variations between studies in severity of COPD, different control groups and different methods of neutrophil isolation.…”
Section: Discussionmentioning
confidence: 95%